Otolith morphology and feeding ecology of an Antarctic 3 nototheniid, Lepidonotothen larseni - Curcio, Nadia Soledad (2013)
This study is based on the analysis of the stomach content and the morphology and morphometry of the three pairs of otoliths (sagitta, asteriscus and lapillus) of Lepidonotothen larseni (Lo¨nnberg) collected at the South Shetland Islands and Antarctic Peninsula during summer, in order to find possible relationships between ontogenetic change of sagittal otolith shape and feeding ecology. Length-weight relationship resulted in a positive allometric growth, with juveniles and adults in good nutritional condition (Le Cren condition index.1), and with a decreasing trend from noon to late evening of the stomach repletion index. The stomach content consisted of several prey, with copepods and amphipods more frequent and abundant in juveniles, whereas euphausiids were in adults. The morphometric analysis of otoliths enabled us to relate different measurements with fish size, and those contributing mostly to separate juveniles from adults were the otolith and rostrum length and their percentage (R index). Juveniles proportionally showed a shorter and wider sagitta than adults reflected in a major E index because of a rounded shape and a minor R index because of a less developed rostrum. This pattern can be tentatively linked to the different habitat of juveniles and adults of this species, being respectively pelagic and epibenthic, as also evidenced by the 24 ontogenetic change of feeding habits.